"Unveiling cellular immunity: A study on diabetes mellitus patients with gangrene wounds" - Meri, Meri; Meisya F, Lisna; Liswanti, Yane (Science Midwifery, 2024)
Diabetes mellitus experiences disruptions in the immune system, particularly in cellular components. Cells crucial in inflammatory conditions are represented by granulocytes and lymphocytes. However, further explanation is needed regarding the quantities of these cells, especially in diabetes mellitus with gangrene. The research method employed is a quantitative descriptive cross-sectional approach. The research population consists of diabetes mellitus patients with gangrene wounds. The sample size contributing to the study is 14 individuals, representing the total population. Exclusion criteria include patients with other systemic infections. The research findings reveal the frequency distribution of the average granulocyte cell count to be 65.47%, with a standard deviation (SD) of 8.52, a minimum value of 53.3%, and a maximum value of 83.4%. The average lymphocyte cell count is 25.7%, with an SD of 7.97, a minimum value of 10.8%, and a maximum value of 38.7%. In conclusion, the study indicates an increased granulocyte count in 4 individuals or 26.6%, while 10 individuals or 71.4% exhibit normal counts. Conversely, the normal lymphocyte count is observed in 11 individuals or 78.6%, whereas 3 individuals or 21.4% exhibit low counts.